2021
DOI: 10.3390/educsci11100583
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Teachers’ Classroom Practices: The Case of Secondary Education Science Teachers

Abstract: Teachers’ knowledge rooted in classroom practices guides their actions when dealing with a specific subject matter. To assess the quality of these practices, a close examination of the “classroom reality” is needed. The present study, which was carried out in Greece, investigates secondary science teachers’ practices. To record these practices, we used special classroom observation tools as well as questionnaires to record students’ views of their teachers’ practices. The observation tools and the student ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For example, Chapoo et al (2014) found that their case teacher confidently implemented all five PCK components (knowledge of students' understanding of science, orientations toward science teaching, curriculum, assessment, and instructional strategies). Also, the finding that teachers' enacted knowledge of conceptual teaching strategies to a moderate level contradicts Sofianidis and Kallery (2021), who reported that teachers' knowledge of teaching approaches was weak.…”
Section: Students' Perceptions Of Teachers' Epckmentioning
confidence: 76%
See 2 more Smart Citations
“…For example, Chapoo et al (2014) found that their case teacher confidently implemented all five PCK components (knowledge of students' understanding of science, orientations toward science teaching, curriculum, assessment, and instructional strategies). Also, the finding that teachers' enacted knowledge of conceptual teaching strategies to a moderate level contradicts Sofianidis and Kallery (2021), who reported that teachers' knowledge of teaching approaches was weak.…”
Section: Students' Perceptions Of Teachers' Epckmentioning
confidence: 76%
“…The results support Halim et al (2014), who reported that low-achieving students did not consider teachers' knowledge of conceptual representation as significant for effective instruction. However, Sofianidis and Kallery (2021) found that knowledge of representations was among the teachers' strong points. Therefore, teachers need adequate knowledge of representation to present content in a clear and understandable way.…”
Section: Students' Perceptions Of Teachers' Epckmentioning
confidence: 97%
See 1 more Smart Citation
“…This type of research allows the use of survey tools to obtain data and it also allows the quantitative analysis of data using frequency count, percentages, means, and other statistical methods. Atmowardoyo [37]; Sofianidis and Kallery [38] have used it in their research and found it to be useful in answering "how" questions. The population of the study involved all senior secondary two students (SS2) in Ondo, Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…In the eligibility phase, the research members were assigned specific publications that they were required to read and then discussed with the team the eligibility of those publications regarding the research topic based on their titles, abstracts and keywords. This phase resulted in a total of 75 publications being excluded from the data collection due to some reasons, including irrelevant topics (Shaw et al, 2014;Sofianidis & Kallery, 2021;Vekiri, 2013), mismatching research subjects, either computer science teachers specifically (Nakajima & Goode, 2019;Ravitz et al, 2017) or higher education teachers/students (Pekdag et al, 2021).…”
Section: Databasementioning
confidence: 99%